Factors affecting the satisfaction and choice of specialization in medical students: A case study in Babol university of medical sciences - Sara Salehian; Mohammad-Ali jahani; Khadijeh Ezoji; Ali Bijani; Hossein-Ali Nikbakht (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: The assessment of the interest of medical students in continuing their studies in specialized fields and the factors affecting it can play a strategic role in macro educational planning. Therefore, the present study aimed to assess the level of academic interest and the factors affecting the choice of specialty in medical students of Babol University of Medical Sciences. Materials & Methods: In this applied cross-sectional study, the study population included incoming medical students from 2009 to 2017 in clinical preparation, stager, and internship. The participants were selected by the convening sampling, and the research tool was a researcher-made questionnaire. Data were collected and entered into SPSS software (version 22) and analyzed by related tests at a significance level of p-value ≤ 0.05. Results: The mean age of students was 23.02±1.65 years, and124 (61/4%) students were female. Moreover, 96.6% of students wanted to continue their studies in residency. Social status in 142 (70.3%) students and lack of free time in 97 (48%) students, respectively, were the most important positive and negative influential factors in the selection of medicine as the field of study. Three fields of cardiology (n=9; 145.1%), radiology 84 (n=84; 41.6%) and ophthalmology (n=82; 40.6%) were the first three priorities. No statistically significant difference was observed in gender in any of the specialties, except urology (P=0.008). Conclusion: Interest, social status, income, years of study, and hospital attendance status were the factors affecting the choice of residency among medical students.